Putting vulnerability to climate change on the map: a review of approa ches, benefits, and risks - Preston, Benjamin L.; Yuen, Emma J.; Westaway, Richard M. (Sustainability Science; Dordrecht, 2011)
There is growing demand among stakeholders across public and private i nstitutions for spatially-explicit information regarding vulnerability to climate change at the local scale. However, the challenges associa ted with mapping the geography of climate change vulnerability are non -trivial, both conceptually and technically, suggesting the need for m ore critical evaluation of this practice. Here, we review climate chan ge vulnerability mapping in the context of four key questions that are fundamental to assessment design. First, what are the goals of the as sessment? A review of published assessments yields a range of objectiv e statements that emphasize problem orientation or decision-making abo ut adaptation actions. Second, how is the assessment of vulnerability framed? Assessments vary with respect to what values are assessed (vul nerability of what) and the underlying determinants of vulnerability t hat are considered (vulnerability to what). The selected frame ultimat ely influences perceptions of the primary driving forces of vulnerabil ity as well as preferences regarding management alternatives. Third, w hat are the technical methods by which an assessment is conducted? The integration of vulnerability determinants into a common map remains a n emergent and subjective practice associated with a number of methodo logical challenges. Fourth, who participates in the assessment and how will it be used to facilitate change? Assessments are often conducted under the auspices of benefiting stakeholders, yet many lack direct e ngagement with stakeholders. Each of these questions is reviewed in tu rn by drawing on an illustrative set of 45 vulnerability mapping studi es appearing in the literature. A number of pathways for placing vulne rability mapping on a more robust footing are also identified. [PUBLIC ATION ABSTRACT]
Keywords: Climate change; Mapping; Risk assessment; Sustainable development